PENGARUH MANAJEMEN KONFLIK DAN PERUBAHAN PERILAKU TERHADAP KINERJA GURU SMP NEGERI SE-KOTA LUBUKLINGGAU - Rudi Erwandi (LP4MK STKIP PGRI Lubuklinggau, 2017)
The objective of this research is to study the effect of conflict management, and attitude change on teachers’ Job Performance. The research was conducted at Junior High School Lubuklinggau. This study used a survey method with path analysis for testing hypothesis. There were 84 teachers taken as the samples of the research by simple random sampling. Data analysis indicate that: (1) there is direct effect of conflict management on Job Performance; (2) there is direct effect of attitude change on job performance; (10) there is direct effect of conflict management on attitude change. Based on these findings teachers’ job performance can be enhanced through conflict management, and attitude change.